FUNDAMENTALS OF THE PHYSICAL EDUCATION SYSTEM - Abbasov Bakhadir Asatillayevich (Western European Studies, 2024)
Physical culture is an organic part of universal culture, its independent field. At the same time, it is a specific process and result of human activity, a means and a way of physical improvement of the personality. Physical culture affects the vital aspects of an individual, obtained in the form of inclinations that are genetically transmitted and develop in the course of life under the influence of upbringing, activity and the environment
Keywords: Physical education; physical culture; modern approach